Program KKN Sebagai Upaya Peningkatan Masyarakat yang Sehat dan Lingkungan Bersih di Desa Srijaya Kecamatan Tambun Utara Kabupaten Bekasi - Prasmoro, Alloysius Vendhi; Supratman, Jasan; Spalanzani, Widya; Rosihan, Rifda Ilahy; Aditya, Muhammad (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Health and environmental cleanliness problems are still the main problems in almost all villages in general. With this problem, the village hopes for a solution by collaborating with several parties. One of the collaborations is the KKN program implemented by the campus, namely the KKN program implemented by the Faculty of Engineering, Bhayangkara University, Jakara Raya, which is implemented in Srijaya Village, North Tambun District, Bekasi Regency, West Java Province. Based on surveys and observations in Srijaya Village, the initial results of the main program in the health sector are the prevention and management of stunting. Meanwhile, in the field of environmental hygiene, there are major problems with sanitation and inappropriate waste disposal. Based on the results of these observations, it was agreed that the KKN work program was counseling on the prevention and handling of stunting, implementing community service work for village cleanliness, making trash cans in easy-to-reach areas, and installing RT/RW name signs. The implementation process involves village officials, village midwives, village residents and the KKN team. The results of the implementation have had a positive impact on the residents of Srijaya village, namely that the villagers understand better how to prevent and handle stunting, the importance of cleanliness and sanitation and concern for environmental cleanliness which must be improved.